2013
DOI: 10.1038/srep01583
|View full text |Cite
|
Sign up to set email alerts
|

The Network Organization of Cancer-associated Protein Complexes in Human Tissues

Abstract: Differential gene expression profiles for detecting disease genes have been studied intensively in systems biology. However, it is known that various biological functions achieved by proteins follow from the ability of the protein to form complexes by physically binding to each other. In other words, the functional units are often protein complexes rather than individual proteins. Thus, we seek to replace the perspective of disease-related genes by disease-related complexes, exemplifying with data on 39 human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 50 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…55 To investigate whether Mtp-proteins prefer to form complexes or whether complex-forming proteins prefer to be post-translationally modified, we analyzed 1845 human complexes, comprising 8842 components, retrieved from the CORUM database (Comprehensive Resource of Mammalian Protein Complexes 56 ). Among all components, 7173 (92%) of them were proteins with PTM sites.…”
Section: Exploratory Analysis On Mtp-proteins: Mtp-proteins Are Enricmentioning
confidence: 99%
“…55 To investigate whether Mtp-proteins prefer to form complexes or whether complex-forming proteins prefer to be post-translationally modified, we analyzed 1845 human complexes, comprising 8842 components, retrieved from the CORUM database (Comprehensive Resource of Mammalian Protein Complexes 56 ). Among all components, 7173 (92%) of them were proteins with PTM sites.…”
Section: Exploratory Analysis On Mtp-proteins: Mtp-proteins Are Enricmentioning
confidence: 99%
“…It has been reported that certain proteins are cancer-associated [ 45 , 46 ]. Therefore, identifying the common proteins presented by cancer cells and investigating their relevance to cancers may provide clues about cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…One of the challenges in constructing accurate CCIs networks is the lack of sufficient structural information, which can resolve the availability of protein interaction-bindings site interfaces. Although there is an increasing amount of 3D structures of protein complexes being deposited into the protein data bank (PDB) [87], the coverage is still very sparse Human [169,170] across all proteomes, including human [88]. Using the protein interaction networks as they exist currently, it is unknown whether a hub protein, with many interactions in the network, uses single or multiple-binding site interfaces.…”
Section: Understanding the Network Organization And Structure Of Compmentioning
confidence: 99%